A Comprehensive Partnership Approach Increasing High School Graduation Rates and College Enrollment of Urban Economically Disadvantaged Youth. (July 2015) - Morgan, Yvette; Sinatra, Richard; Eschenauer, Robert
Described is a 4-year model of a Gaining Early Awareness and Readiness for Undergraduate Program (GEAR UP) offered to 294 academically and economically disadvantaged students and their parents during in- and out-of-school time activities through partnerships forged with school personnel and community-based agencies. In an urban high school where the annual graduation rate was below 60%, the graduation rate of the GEAR UP students of whom 60% were Hispanic and African American was 95%, while 58% enrolled in a postsecondary institution soon after graduation. Regardless of the time spent in three participatory conditions in the out-of-school time activities, 12th graders commonly believed that the program significantly helped them complete high school, prepared them for college, and showed them that adults cared about their future. A five-item survey completed by parents also revealed a number of highly significant findings. Quantitative, focus group, and interview findings corroborated and supported each other.